Chaotic dead-zone eliminating and time delay signature concealing optoelectronic chaotic laser system based on balanced detection - Li, Mi; Wang, Yisi; Sun, Xun; Fu, Wanwang; Song, Yuejiang; Chen, Xiangfei (Optical engineering, 2024)
Chaotic optical communications provide high security for physical layer encryption. We propose a chaotic laser communication system based on a balanced detection optoelectronic delayed feedback system, which has a higher performance compared with one based on single-photodiode detection. Our numerical analysis proves that dynamic behaviors are achieved at only half feedback gain, and the safety hazard chaotic dead zone is eliminated. The generated chaos features high pseudo-randomness and a good capacity to conceal time-delay signatures, which makes it hard for an unauthorized party to remove the chaotic carriers. 10 Gbps message hidden in wideband chaotic carries is transmitted back-to-back, and the BER 10−1 of the eavesdropper achieved at a low feedback gain β=3.2 proves its high confidentiality. Our proposed system has the potential to promote chaotic laser systems to practical appliances with simple structure and high performance.